Towards a climate-resilient Jakarta: An analysis of the resilience thinking behind Jakarta's current public policy approach to climate-related hazards - Jakob Haushofer (Südwind-Verlag, 2018)
Climate change presents undoubtedly one of the greatest contemporary threats both for the planet and for humankind. Climate change adaptation is therefore a challenge that with good reason was included in the Agenda 2030 of the United Nations. SDG 13 stipulates to take urgent action to combat climate change and its impacts, in particular by strengthening resilience and adaptive capacity to climate-related hazards and natural disasters in all countries. SDG 11 calls for governments and public authorities to make cities and human settlements inclusive, safe, resilient and sustainable, and in particular "by 2030, to significantly reduce the number of deaths and the number of people affected […] by disasters, including water-related disasters, with a focus on protecting the poor and people in vulnerable situations". Against this background, research which aims at enhancing our understanding of how to improve the climate resilience of megacities and coastal urban agglomerations is highly topical and of particular relevance to both climate action and development cooperation. The master thesis by Mr. Jakob Haushofer provides a thorough and empirically grounded analysis of climate resilience policies in Jakarta. As such, it does not only enhance our understanding of a specific conception of resilience policies in a megacity of South-East Asia, but provides important general lessons on the challenges for climate resilience policies in large urban agglomerations both in the Global South and North.
Keywords: 360